(untitled) (National Administration Journal, 2025)
The purpose of this study is to understand aspects related to the link between entrepreneurial characteristics, human capital, networks and the business environment in the performance of academic spin-offs. For this study, seven in-depth interviews were conducted with founding members of the entrepreneurial team of university academic ventures, which were processed and analyzed using the NVIVO 12 software. The results of the study show that the products generated from the entrepreneurship arise by the motivation to show the work that is done, and this has a direct relationship with performance. Likewise, the interdisciplinary team contributes to the development of specific functions, improving efficiency and therefore also performance. The social networks of the entrepreneurial team contribute to the evolution and opportunities to improve the performance of spin-offs and the immediate business environment benefits the development and performance of academic spin-offs